Myosteatosis predicts the prognosis of patients with ST-elevation myocardial infarction who undergo emergency percutaneous coronary intervention - Wang, Junqian; Zhou, Lingshan; Yang, Yuan; Wang, Yiqing; Liang, Yan; Wang, Tong; Li, Jinkui; Bai, Ming (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the value of myosteatosis in predicting the prognosis of patients with ST-elevation myocardial infarction (STEMI).MethodsThis retrospective study involved 324 patients with STEMI who had undergone emergency percutaneous coronary intervention (PCI) at our institution between 2017 and 2020. Myosteatosis was assessed using mean muscle attenuation (MMA). Cox proportional hazards models were utilized to identify prognostic determinants required for the construction of a nomogram. The discriminatory performance of the nomogram was assessed via calibration curve analysis.ResultsAmong the 324 patients, 35 patients (10.8%) died during the follow-up period. A lower MMA was observed in patients who died after discharge. In the multivariate analysis, MMA was identified as an independent prognostic factor. The optimal cutoff MMA value for the prediction of all-cause mortality was 32.5 Hu. The patients were classified into high (≥32.5, n=208) and low (<32.5, n=116) MMA groups. Compared with patients in the high-MMA group, patients in the low-MMA group had shorter overall survival (OS). Finally, nomograms for OS that integrate the MMA and other clinical parameters were constructed. The calibration analysis revealed that the nomograms accurately predicted the 1-, 3- and 5-year OS rates of patients.ConclusionsMyosteatosis was associated with poorer survival outcomes in STEMI patients who underwent emergency PCI. A novel risk model comminating myosteatosis with other common clinical indicators can accurately predict the prognosis of STEMI patients.